Temporizing External Fixation vs Splinting Following Ankle Fracture Dislocation. (February 2020) - Wawrose, Richard A.; Grossman, Leonid S.; Tagliaferro, Matthew; Siska, Peter A.; Moloney, Gele B.; Tarkin, Ivan S.
Background: Closed reduction and splinting followed by outpatient management is standard of care for temporizing most ankle fractures. However, ankle fracture-dislocation potentially warrants a different approach based on the propensity for loss of reduction. The purpose of this study was to determine the rate of complications associated with closed reduction and splinting of unstable ankle fracture-dislocations. Further, we sought to determine the efficacy of immediate external fixation as an alternative to splinting in cases too swollen for acute operation. Methods: This retrospective chart review analyzed all ankle-fracture dislocations that came through a large health care system from 2008 to 2018. Patients managed with acute open reduction internal fixation (ORIF) and open fractures were excluded. In patients managed late, the cohorts were divided into those temporized with closed reduction/splinting vs external fixation. Reduction quality and splint technique were additionally assessed in splinted patients. A total of 354 closed ankle fracture-dislocations were identified: 298 patients (84%) underwent ORIF within 48 hours and were excluded; 28 (15 female/13 male, average age 46.8 years) were placed in an external fixator and 28 (22 female/6 male, average age 57.2 years) were reduced, splinted, and discharged. Results: At follow-up, 14 of the patients (50%) in the splint group developed loss of reduction and 5 of these patients (17.6%) developed anteromedial skin necrosis from skin tenting. None of the patients in the ex-fix group developed loss of reduction or skin necrosis. The rate of redislocation and the rate of development of skin necrosis was statistically higher in cases temporized with a splint versus an external fixator ( P < .01 and P = .05, respectively). Conclusion: We found that in ankle fracture-dislocations not treated with acute ORIF, splint immobilization was associated with an increased risk of complications, including redislocation and skin necrosis, when compared to a temporizing external fixator. Level of Evidence: Level III, retrospective comparative study.